(untitled) (Research, Society and Development, 2019)
The present work seeks to present the Gamification practice - inserted within Education 3.0 - from a contextualization on all models of education, throughout history, until reaching the Digital Age, where a shocking problem arises: the students’ demotivation studies, once observed by them that this reality does not follow the technological scenario that surrounds them. In this way, the work has the general objective of answering the question of "Why Gamificar?", And the specific objectives are to present the Gamification practice and its concept as a bet of Education 3.0 to engage the technologies in order to solve the indicated problem, as well as the benefits of integrating this practice into teaching. The research was done in a qualitative way, and the methodology used was exploratory and descriptive. As a result, it was possible to find the benefits of integrating Gamification into teaching, and how it can solve the observed problem, concluding that the practice may be one of Education 3.0’s bidders, adapting dynamically to students and technology.